Integrated SOM Multi-Attribute Optimization and Seismic Waveform Inversion for Thin Sand Body Characterization: A Case Study of the Paleogene Lower E3d2 Sub-Member in the HHK Depression, Bohai Bay Basin - Jing Wang; Dayong Guan; Xiaobo Huang; Youbin He; Hua Li; Wei Xu; Rui Liu; Bin Feng (Applied Sciences)
Thin-bedded beach-bar reservoirs in the continental faulted basins of eastern China hold significant potential, yet pose challenges for unconventional hydrocarbon development due to their thin-layer characteristics and heterogeneity. This study focuses on the Paleogene Lower E3d2 Sub-member in the HHK Depression, Bohai Bay Basin as a case study. We propose an innovative technical framework integrating Self-Organizing Map (SOM) multi-attribute optimization with seismic waveform inversion. Petrophysical analysis demonstrates that waveform-indicated inversion can detect 1.8–3.0 m thin sandstones, achieving a 90.2% mean match rate (95% CI: 87.5–92.7%, n = 12; bootstrap resampling) for training wells and 81.5% (95% CI: 76.8–85.3%, n = 11) for validation wells. By integrating SOM seismic attribute clustering with seismic waveform inversion, we were able to delineate microfacies boundaries with precision, enhancing the visibility of beach-bar sand body distributions. This methodology establishes a new paradigm for thin-bed sandstone prediction in low-well-control areas, providing critical support for geological interpretation and resource evaluation in complex depositional systems.